Total synthesis of isatindigotindoline C. Issue 11 (6th March 2020) - Siitonen, Juha H.; Lira, Sherlin; Yousufuddin, Muhammed; Kürti, László
Abstract : Total synthesis of isatindigotindoline C is achieved in two steps using a biomimetic 1, 3-dipolar cycloaddition reaction as the key step. Abstract : Total synthesis of isatindigotindoline C, a 3, 3′-spiropyrrolidine oxindole alkaloid, is achieved in two steps using an exo -selective decarboxylative 1, 3-dipolar cycloaddition as the key step. The synthesis verifies the originally assigned relative anti -stereochemistry for the bis-oxindole core of isatindigotindoline C.